SIGNIFICANCE OF PERIPHERAL ARTHRITIS IN ANKYLOSING SPONDYLITIS - Sh. F. Erdes; E. V. Volnukhin (Научно-практическая ревматология, 2014)
Objective: to elucidate the role of peripheral arthritis in ankylosing spondylitis (AS) and its impact on therapy choice in daily practice of rheumatologists. Subjects and methods. The investigation enrolled 330 consecutive patients with AS referred to rheumatologists during 4 months in 24 cities and towns of the Russian Federation. A specially designed clinical schedule was filled out for all the patients. Results. Peripheral arthritis was present in 47% of patients, including in 17 and 46% who had upper and lower limb joint involvement, respectively. Patients with peripheral arthritis had higher ESR, BASDAI and ASDAS-ESR levels. They were also found to have more marked functional disorders than the patients with its isolated axial variant. The clinical signs of hip joint involvement were detected in 56% of the patients and they were bilateral in 43%. In the rheumatologists' opinion, 24 (8%) needed total hip joint replacement. Conclusion. Peripheral arthritis aggravates AS.